Exploring Integrated Energy Action Plans for a Sustainable Transition of the Municipality of Cesena. (2017) - De Miglio, Rocco; Chiodi, Alessandro; Burioli, Sofia; Giovannini, Elena; Gargiulo, Maurizio
Abstract: An application of the innovative city planning method, developed within the EU FP7 project InSMART, is applied to the municipality of Cesena (Italy). A multi-model approach is used to explore and rank alternative plans (combinations of actions and measures) towards the sustainable development of the municipality, with a particular focus on the residential and transport sectors. On the basis of the possible space of decisions of the municipality (which can be seen as "urban planner", as "regulator", as "provider of support and information", as "consumer" and as "supplier" of energy), alternative planning hypotheses have been prepared and tested making use of a city-energy system model and scenario analysis. Scenarios are built around different themes with the aim of exploring the potential benefits (or drawbacks) of the combination of specific "competitive" projects, actions, standards, targets. A reference development of the local system is assumed to be modified through six combinations of actions and measures aiming at representing six pillars of alternative pathways towards the sustainability. Figures below report the key themes and hypotheses taken into consideration in the planning exercise. Once the dynamic pictures of the urban system are produced (one per each alternative), a multi-criteria method is used to determine the ranking of the options, evaluated against a set of elements (technological, social, environmental, economic). This stage is still ongoing and will generate the whole dataset (weights, preference functions) required to rank the alternatives in the next few months. All these alternative strategies are designed with the involvement of the municipality of Cesena, to directly respond their needs of knowledge about potential impacts of different action plans. Compared to the existing city strategic energy action plans, the advantage of the outputs of this approach is the fact that multiple future energy scenarios are analysed and cross-compared and "integrated" strategies ranked.